Blasphemy as a Criminal Offence: Legal Transformation in Indonesia from Colonial Era to Modern - Rokhmad, Abu; Saifudin, Saifudin; Sunandar, Sunandar; Nurdin, Nazar (Universitas Islam Negeri Walisongo Semarang, 2024)
This research is motivated by the persistence of religious offenses, which serve as the state’s primary legal instrument for prosecuting acts of blasphemy. This situation raises fundamental conceptual issues regarding the definition and application of blasphemy as a criminal offense. The study aims to examine the historical development and transformation of blasphemy offenses within Indonesia’s legislative framework, from the colonial period to the modern era. The enforcement of blasphemy laws in practice has drawn substantial criticism, particularly concerning potential violations of human rights and freedom of religion. The findings indicate that religious offenses are regulated under the Supreme Court Circular Letter of 1964 and Law No. 1 of 1965 on the Prevention of Religious Deviations and the Maintenance of Religious Harmony. Blasphemy crimes are further codified in the Indonesian Criminal Code and Law No. 11 of 2008 on Electronic Information and Transactions. The concept of blasphemy in the Criminal Code establishes it as a core element of criminal liability, wherein religion is not merely incidental but a constitutive element of the offense itself. The protection of religious freedom is influenced by the plurality of definitions of religion, interpretations of human rights, and the evolving understanding of legal safeguards for fundamental freedoms. Penelitian ini dilatarbelakangi oleh keberlanjutan pengaturan tindak pidana agama yang berfungsi sebagai instrumen hukum utama negara dalam menuntut pelaku penodaan agama. Kondisi ini menimbulkan persoalan konseptual mendasar mengenai definisi dan penerapan penodaan agama sebagai tindak pidana. Studi ini bertujuan untuk menelusuri perkembangan historis dan transformasi pengaturan tindak pidana penodaan agama dalam kerangka legislasi Indonesia, mulai dari masa kolonial hingga era modern. Penerapan hukum penodaan agama dalam praktiknya banyak menuai kritik, terutama terkait potensi pelanggaran hak asasi manusia dan kebebasan beragama. Hasil penelitian menunjukkan bahwa tindak pidana agama diatur dalam Surat Edaran Mahkamah Agung Tahun 1964 dan Undang-Undang Nomor 1 Tahun 1965 tentang Pencegahan Penyalahgunaan dan/atau Penodaan Agama serta Pemeliharaan Kerukunan Hidup Antar Uat Beragama. Selain itu, tindak pidana penodaan agama juga dikodifikasikan dalam Kitab Undang-Undang Hukum Pidana (KUHP) dan Undang-Undang No. 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik. Konsep penodaan agama dalam KUHP menempatkan agama bukan sekadar unsur tambahan, tetapi sebagai elemen konstitusi dari tindak pidana itu sendiri. Perlindungan terhadap kebebasan beragama dipengaruhi oleh keragaman definisi agama, interpretasi hak asasi manusia, serta pemahaman yang terus berkembang terhadap jaminan hukum bagi kebebasan fundamental. Keywords: Blasphemy; Criminal Offense; Religious Crime; Legal Transformation